Definition of Technologies: Interconnection between Information, Educational and Production Technologies - Rakhimov Oktyabr Dustkabilovich; Salomova Marguba Mamatkulovna (Lembaga Yasin AlSys, 2026)
This article examines the conceptual definitions of technology and clarifies related concepts, including technological cluster, technological park, and technology transfer. It further substantiates the distinction between bulk technology and nanotechnology and provides a substantive analysis of production, pedagogical, and information technologies. Drawing on theoretical analysis, the article reviews definitions of pedagogical technology proposed by foreign and local scholars and formulates an authorial definition of pedagogical technology. The findings establish fundamental interconnections among production, information, and pedagogical technologies, demonstrating that these domains are not isolated but mutually reinforcing within broader technological development. The article concludes that a clearer conceptual understanding of technology and its related categories is essential for explaining how different technological domains interact and contribute to educational, informational, and production processes. This study contributes to technology and education literature by systematizing key technological concepts and offering a theoretical basis for understanding the interrelationship between production, information, and pedagogical technologies. Keywords: Technology; Technological Cluster; Technology Transfer; Pedagogical Technology; Information Technology